Experimental investigation on the effect of solid particle erosion on the water droplet erosion damages for blade materials - Juan Di; Jun Ji; Jin Xu; Zhi Li; Ke Ning; Chao-yi Peng; Jian-feng Wang (Scientific Reports)
Abstract In this paper, the influence of solid particle erosion on the water droplet erosion is explored based on the self-developed erosion test system and high-speed rotating waterjet test rig. The results show that the WDE morphology exhibited distinct structural divergence: substrates displayed stepped fibrous textures (10–20 μm), while the surface presented honeycomb-like stalactite peak cluster structure with each stalactite petal about 2 μm, which is close to the natural stalactite morphology. Besides, it is found that the regular texture or mesh structure of the machined surface is more conducive to the diversion and expansion of the liquid flow than that of the uneven and irregular structure surface formed by the solid particle erosion, making more serious erosion damage of the latter. For martensite substrate and stellite cladding materials, the differences are 5.87 and 2.52 times, respectively.